2019
DOI: 10.1002/adfm.201902023
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Separators for High‐Performance Lithium Ion Batteries Enabled by Chemical Modifications

Abstract: Natural polymer nanofibers are attractive sustainable raw materials to fabricate separators for high-performance lithium ion batteries (LIBs). Unfortunately, complicated pore-forming processes, low ionic conductivity, and relatively low mechanical strength of previously reported natural polymer nanofiber-based separators severely limit their performances and applications. Here, a chemical modification strategy to endow high performance to natural polymer nanofiber-based separators is demonstrated by grafting c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…The electrochemical performances were compared with the data reported previously, showing superior comprehensive performance (Table S1). ,,, …”
Section: Resultsmentioning
confidence: 99%
“…The electrochemical performances were compared with the data reported previously, showing superior comprehensive performance (Table S1). ,,, …”
Section: Resultsmentioning
confidence: 99%
“…Recently, some studies revealed that functional materials derived from biomass were very promising for use as electrodes and/or separators for electrochemical energy storage. [20][21][22][23][24] For instance, Yu et al recently reported a chitin nanober membrane (CNM) derived from prawn shell for use as a separator in LIBs. 22 The electrochemical performance of LiFePO 4 /Li half-cells with CNM separators was comparable to that of devices based on a commercial PP separator (Celgard 2325).…”
Section: Introductionmentioning
confidence: 99%
“…The reactions release a large amount of heat, making the battery temperature exceed the critical temperature (about 150°C) that the battery can withstand. The increase in temperature will in turn accelerate these chemical reactions 10–13 . Too much heat and combustible gases will be released into the battery in a short time, causing the battery to rupture, ignite and even explode.…”
Section: Introductionmentioning
confidence: 99%